2021
DOI: 10.1021/acs.jmedchem.1c00374
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Carbocyclic Pyrimidine Cyclic Dinucleotide STING Agonists for Antitumor Immunotherapy Using Systemic Intravenous Route

Abstract: Stimulator of Interferon Genes (STING) plays an important role in innate immunity by inducing type I interferon production upon infection with intracellular pathogens. STING activation can promote increased T-cell activation and inflammation in the tumor microenvironment, resulting in antitumor immunity. Natural and synthetic cyclic dinucleotides (CDNs) are known to activate STING, and several synthetic CDN molecules are being investigated in the clinic using an intratumoral administration route. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…, ∼2 min in mice), which, along with their poor drug-like properties, significantly limits their overall exposure, tissue distribution, and activity. ,, Accordingly, systemically administered CDNs have proven largely ineffective in limiting tumor growth in mouse tumor models. ,, To improve efficacy for intravenous administration, Vyskocil et al approached some of these limitations by developing a novel carbocyclic STING agonist ( i.e. , 15a ), which comprises carbocyclic nucleotides, cyclopentane instead of ribose, and the imidazole portion of adenine replaced with a pyrimidine ring (Figure ). 15a exhibited a half-life of ∼23.4 min in BALB/c mice when administered intravenously at 1 mg/kg with systemic exposure ( i.e.…”
Section: Drug Delivery Barriers and Pharmacological Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…, ∼2 min in mice), which, along with their poor drug-like properties, significantly limits their overall exposure, tissue distribution, and activity. ,, Accordingly, systemically administered CDNs have proven largely ineffective in limiting tumor growth in mouse tumor models. ,, To improve efficacy for intravenous administration, Vyskocil et al approached some of these limitations by developing a novel carbocyclic STING agonist ( i.e. , 15a ), which comprises carbocyclic nucleotides, cyclopentane instead of ribose, and the imidazole portion of adenine replaced with a pyrimidine ring (Figure ). 15a exhibited a half-life of ∼23.4 min in BALB/c mice when administered intravenously at 1 mg/kg with systemic exposure ( i.e.…”
Section: Drug Delivery Barriers and Pharmacological Challengesmentioning
confidence: 99%
“…328,390,391 Accordingly, systemically administered CDNs have proven largely ineffective in limiting tumor growth in mouse tumor models. 24,196,390 To improve efficacy for intravenous administration, Vyskocil et al approached some of these limitations by developing a novel carbocyclic STING agonist (i.e., 15a), which comprises carbocyclic nucleotides, cyclopentane instead of ribose, and the imidazole portion of adenine replaced with a pyrimidine ring 366 (Figure 12). 15a exhibited a half-life of ∼23.4 min in BALB/c mice when administered intravenously at 1 mg/kg with systemic exposure (i.e., 3.9 μM in plasma collected 5 min after in injection) at or above cellular concentrations required for its activity.…”
Section: Utility and Challenges With Systemic Administration Of Sting...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29a ] The recent study showed that modification of CDN‐mimetic CDNs with a pyrimidine ring improved pharmacokinetics as well as binding affinity, thus enabling systemic administration. [ 31 ] In comparison to the chemical structure of cGAMP, phosphoester was replaced with phosphothioester while the adenine moiety from one of the bases was modified with pyrimidine rings. [ 31 ] This CDN‐mimetic STING agonist was endowed with greater binding affinity with human STING protein and prolonged half‐life in blood plasma, thus showing meaningful anti‐tumor responses in colorectal tumor models.…”
Section: Cgas‐sting‐activating Moleculesmentioning
confidence: 99%
“…ML00960317 is a STING agonist with a synthetic CDN structure (Fig. 1), and it has shown potent antitumor activity in nonclinical tumor models by inducing robust innate and adaptive immune responses (5). Generally, endogenous cGAMP and its synthetic analogs such as ML00960317 have moderate-to-high molecular weight (> 400) and low permeability (Supplemental Table 6) and therefore, uptake transporters play an obligatory role in their pharmacological effects in target cells (6,7).…”
Section: Introductionmentioning
confidence: 99%